Analysis Determinant of Profitability and Their Effect on The Value of Automotive Companies Listed on IDX - Sulistiyani, Sulistiyani; Noor, Salim M (International Journal of Finance Research, 2022)
This study aims to analyze the effect of financial performance on firm value with profitability as an intervening variable. The population in this study are automotive companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The financial performance used in this study is the Dept to Equity (DER), Current Ratio (CR), and company size. The research data is secondary data with an observation period of 5 years. The sampling method used is purposive sampling, where from all automotive companies listed on the IDX selected based on certain criteria. Samples that meet the criteria are 8 companies. The data analysis method used is panel data regression. The results showed that Fixed Effect is the best model. The results of the partial test (t test) of the DER ratio have a negative and significant effect on profitability, CR and firm size have no effect on profitability, while profitability on firm value has no significant effect. Partially DER has a positive effect on firm value, CR and firm size have no significant effect on firm value. The role of profitability as an intervening variable is very important in increasing the effect of DER, CR, and firm size on firm value. The results of the Prob (F-statistic) are 0.000 < 0.005, meaning that together this study which consists of DER, CR, and firm size has a positive and significant effect on firm value.